Genetic Continuity of Bronze Age Ancestry with Increased Steppe-Related Ancestry in Late Iron Age Uzbekistan. (28th July 2021) - Kumar, Vikas; Bennett, E Andrew; Zhao, Dongyue; Liang, Yun; Tang, Yunpeng; Ren, Meng; Dai, Qinyan; Feng, Xiaotian; Cao, Peng; Yang, Ruowei; Liu, Feng; Ping, Wanjing; et al.
Abstract: Although Uzbekistan and Central Asia are known for the well-studied Bronze Age civilization of the Bactria–Margiana Archaeological Complex (BMAC), the lesser-known Iron Age was also a dynamic period that resulted in increased interaction and admixture among different cultures from this region. To broaden our understanding of events that impacted the demography and population structure of this region, we generated 27 genome-wide single-nucleotide polymorphism capture data sets of Late Iron Age individuals around the Historical Kushan time period (∼2100–1500 BP) from three sites in South Uzbekistan. Overall, Bronze Age ancestry persists into the Iron Age in Uzbekistan, with no major replacements of populations with Steppe-related ancestry. However, these individuals suggest diverse ancestries related to Iranian farmers, Anatolian farmers, and Steppe herders, with a small amount of West European Hunter Gatherer, East Asian, and South Asian Hunter Gatherer ancestry as well. Genetic affinity toward the Late Bronze Age Steppe herders and a higher Steppe-related ancestry than that found in BMAC populations suggest an increased mobility and interaction of individuals from the Northern Steppe in a Southward direction. In addition, a decrease of Iranian and an increase of Anatolian farmer-like ancestry in Uzbekistan Iron Age individuals were observed compared with the BMAC populations from Uzbekistan. Thus, despite continuity from the Bronze Age, increased admixture played a major role in the shift from the Bronze to the Iron Age in southern Uzbekistan. This mixed ancestry is also observed in other parts of the Steppe and Central Asia, suggesting more widespread admixture among local populations.